Instability of flow with suspended sediment in an inclined channel - Diep, Nguyen Van; Chung, Dang Huu (Vietnam Journal of Mechanics, 1991)
In this work the authors had studied the instability and nonlinear evolution of steady flow suspended sediment in inclined channel with fixed and plane bed. With the linear analysis- it has been shown that at the critical inclined angle, an arbitrary disturbance will be splinted in three modes 3F0/2, F0/2, F0, in which F0/2 and F0 propagate downstream and deaden while mode 3F0/2 propagates downstream and its form is unchanged. In particular the waves of sediment concentration always propagate downstream with velocity F0 and unchanged form. The nonlinear analysis has shown that the concentration waves propagate downstream with velocity F and deaden when the time t is large.